Confusion and convergence: the Nazi challenge to world order and the CFR response, 1940–1941. Issue 6 (November 2018) - Fletcher, Luke
Abstract Scholars have long debated how influential the Council on Foreign Relations' War and Peace Studies project was on the Roosevelt administration and the State Department, especially in the lead-up to US entry into World War II. But these debates have underemphasized the heterogeneity and even confusion displayed within the WPS after the fall of France. The Nazi successes challenged US conceptions of world order profoundly and forced a serious rethink of the responsibilities that the USA should undertake in order to build a world order consistent with its larger goals. By tracking the divergent paths taken by the four WPS groups over the 12 months that followed the Nazi conquest of Western Europe, this article highlights the uncertainty that the Nazi thrust posed to US elites. And it demonstrates how this uncertainty was resolved by accepting a more proactive and muscular US role in world affairs.